Issues Supervising Family Violence Cases: Advocacy, Ethical Documentation, and Supervisees’ Reactions - McBride, Dawn L. (Canadian Journal of Counselling and Psychotherapy, 2010)
Selected clinical and ethical issues associated with providing supervision involving family violence cases are outlined. It is argued that supervisees helping clients with trauma histories require skills beyond learning how to process the trauma with their clients. Advocacy, social action, and coordinating case conferences are some of the nontypical counsellor skills supervisors may want to teach their supervisees, as some of these topics might not be taught in non-social work counsellor education programs. In addition, the necessity to coach supervisees on how to document trauma-based sessions in a way that balances various ethical and legal responsibilities is extensively discussed. The article concludes with concrete strategies to help supervisees manage their emotional reactions associated with processing stories of family violence.